2019
DOI: 10.14740/jmc3358
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes as a Cause of Spontaneous Bacterial Peritonitis

Abstract: Spontaneous bacterial peritonitis is a common and often serious complication of long standing ascites in the presence of advanced liver disease. We report a case of a 74-year-old woman with alcoholic cirrhosis admitted to our emergency department with a 1-week history of diffuse abdominal pain and increased abdominal perimeter. On physical examination, she had a significant abdominal distention and a positive fluid wave consistent with ascites. A diagnosis of spontaneous bacterial peritonitis was made and empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…However in some studies, combination ampicillin and gentamicin has not been shown to improve outcome or have any impact on mortality, but has been shown to increase adverse events [31] , [32] . Listerial SBP can be treated with a penicillin alone [24] , [33] .…”
mentioning
confidence: 99%
“…However in some studies, combination ampicillin and gentamicin has not been shown to improve outcome or have any impact on mortality, but has been shown to increase adverse events [31] , [32] . Listerial SBP can be treated with a penicillin alone [24] , [33] .…”
mentioning
confidence: 99%